A Heavy Scalar at the LHC from Vector-Boson Fusion - Qiurong Mou; Sibo Zheng (Advances in High Energy Physics)
A hypothetical scalar mixed with the standard model Higgs appears in few contexts of new physics. This study addresses the question what mass range is in the reach of 14 TeV LHC given different magnitudes of mixing angle α, where event simulations are based on production from vector-boson fusion channel and decays into SM leptons through WW or ZZ. It indicates that heavy scalar mass up to 539 GeV and 937 GeV can be excluded by integrated luminosity of 300 fb-1 and 3000 fb-1, respectively, for sin2α larger than 0.04.